Peran Strategis Pemerintah Dalam Regulasi dan Pengawasan Asuransi Kesehatan: Pembelajaran Dari Negara Thailand - Meutya Zahra Eriansyah; Raisha Syahida; Riswandy Wasir (Lembaga Pengembangan Kinerja Dosen, 2025)
Although routine health facility accreditation has been implemented in Indonesia, achieving Universal Health Coverage (UHC) remains a significant challenge. In contrast, Thailand stands out as one of the ASEAN countries that has successfully implemented an effective UHC system, despite facing several obstacles. This study aims to explore the strategic role of the Thai government in developing a national health insurance system that may serve as a valuable reference for Indonesia. This research adopts a qualitative approach using literature review and secondary data analysis, with data collected from eight selected journal articles. The findings reveal that the Thai government has effectively strengthened the synergy between participatory and responsive governance in regulating and overseeing health insurance. Public engagement is conducted through annual public consultations and the inclusion of legislators in key bodies such as the Security Council, the Standards and Quality Control Council, and the Social Security Committee. Oversight mechanisms are implemented through regular quality control, public disclosure of reports, periodic financial audits, and by ensuring that the public has easy access to report problems or complaints. Based on these findings, it can be concluded that the strategic role of the Thai government in involving the public in health insurance regulation has not been fully realized in Indonesia. Oversight mechanisms such as financial audit transparency and public access to information on the performance of insurance fund management, as practiced in Thailand, are still lacking in Indonesia. Lessons from Thailand’s approach may provide valuable insights for strengthening oversight and enhancing public involvement in Indonesia's pursuit of UHC.